Protein kinase R regulates pancreatic ductal adenocarcinoma progression by modulating the cell cycle via GADD45A - Yuki Numata; Mitsuhito Koizumi; Takao Watanabe; Osamu Yoshida; Yoshio Tokumoto; Kaori Marui; Sho Ishikawa; Masahito Kokubu; Yusuke Okujima; Yoshiki Imamura; Teruki Miyake; Teru Kumagi; et al. (Scientific Reports)
Abstract Protein kinase R (PKR) functions both as a promoter and inhibitor in various cancers; however, its role in pancreatic ductal adenocarcinoma (PDAC) remains unclear. We investigated the role of PKR in PDAC. PKR expression in PDAC cell lines was assessed using real-time reverse transcriptase polymerase chain reaction and western blotting. The effect of PKR on cell proliferation was examined using MTS assay. To determine the mechanisms of PKR’s action on PDAC, RNA-sequencing analysis was performed, and the effects of PKR knockdown on cell cycle progression and apoptosis in PDAC cells were examined using flow cytometry. PDAC cell lines transfected with PKR-targeting short interfering RNAs or treated with PKR inhibitors exhibited significantly reduced proliferation. RNA-sequencing analysis revealed substantial upregulation of GADD45A expression upon inhibition of PKR expression. Following PKR silencing, cell cycle analysis showed marked accumulation of cells in G1 phase, consistent with the role of GADD45A as a cell cycle regulator. Proliferation inhibition caused by PKR knockdown was reversed by downregulation of GADD45A, suggesting that PKR and GADD45A interact to regulate PDAC cell growth. PKR promotes PDAC cell proliferation by modulating the cell cycle via regulation of GADD45A expression, demonstrating its potential as a therapeutic target for PDAC.